'Curtains, music and stages' in Zoom theatre: framing devices in Coney's Telephone. Issue 1 (2nd January 2023) - Chen, Lin
ABSTRACT: Coney's interactive digital piece Telephone, created and performed by Tassos Stevens, was premiered in April 2020 amidst the first lockdown in England. Performed via the videoconferencing platform Zoom, it employs conventional framing devices such as a prologue, opening music, a surrogate stage curtain and a virtual theatre bar. This paper intends to examine the functions of these theatrical conventions in the Zoom production. The author argues that these devices are used not only for their usual dramatic purposes, but are also adapted with new functions for digital media and the special circumstances of the pandemic. They inform the spectators of the dramatic situation and the contextual situation of lockdown, in order to provide crucial technical instructions, to frame the performance within familiar domestic spaces and cyberspace, and to seek their understanding of the unusual form in which the piece is made. By the explicit and emphatic use of these conventional framing devices, the production activates the audience's consciousness of the theatrical dual orders of presence and representation, so as to construct a live theatre experience and senses of co-presence and togetherness, which are all the more significant during a time of theatre closure and social distancing.